EVOLUTION OF EDUCATIONAL PARADIGMS IN MODERN SCIENTIFIC DISCOURSE - Batechko Nina; Mykhailichenko Mykola (Borys Grinchenko Kyiv Metropolitan University, 2021)
The article analyzes the phenomenon of the educational paradigm as a philosophical and pedagogical category. The article states the importance of educational paradigms for the modernization and development of the educational sphere as a catalyst for shifts and qualitative transformations in it. The aim of the article is the methodological substantiation of the educational program in the context of modern transformations in society. Attention has been focused on the definitions «paradigm», «pedagogical paradigm», «educational paradigm». The discourse of scientists about these concepts has been provided and the general and distinctive shades between them have been clarified. Various types of educational paradigms have been highlighted and grouped depending on the goals they carry in their contents. Depending on the analysis carried out, it has been indicated that an educational paradigm always, in any historical era, acts as a paradigm idea of the development of education. It has been noted that the mission of pedagogy is in the change and dynamics of the educational paradigm as the one which provides the basis for innovative approaches to the development of education, the contents and organization of training and interaction among the main subjects of education. The synergetic paradigm has been indicated as a new and innovative educational paradigm. Education can be considered as a synergetic system whose self-organization processes can be fully described by such categories as bifurcations, fluctuations, attractors, dissipative structures, etc. This circumstance leads to a revision of the established, traditional ideas about education and makes the basis for qualitative changes in its development.